THE NEED TO USE CREATIVE THINKING METHODS FOR ENTERPRISE DEVELOPMENT IN THE MODERN COMPETITIVE ENVIRONMENT - BARKOVA, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the study was to determine the main methods of developing the creative thinking of enterprise employees under the conditions of increasing competition. The article states that creativity is a competitive advantage of any enterprise and argues that companies should solve their problems in an innovative way with the help of ideas that allow them to constantly adapt to the external environment. An analysis of research was carried out, which made it possible to highlight creativity as one of the most important leadership qualities for CEOs, which surpasses even decency and global thinking. The benefits of developing creativity have been highlighted, including increased revenue, market share, increased employee productivity, improved customer service, fostering innovation, and ultimately financial success. Analyzed and formulated methods of development of creative thinking: brainstorming of ideas, which provides an opportunity to open up and share thoughts and ideas freely, without restrictions and prejudices; mind maps, as a graphical tool that facilitates idea generation and allows you to dive deeper into a concept or topic, narrowing it down to the most specific topics as ideas are broken down into pieces in the process; changing the way of thinking, which means changing the point of view on the issue and opportunities to approach it differently, this will allow the team to open new perspectives on the issue; role playing as the method most useful for coming up with ideas for a product and predicting how it will perform in the market; study of various psychological theories of creativity; learning to ask the right questions around issues related to product features, customer feedback, problem nature, etc. or using the six thinking hats strategy. The importance of building a program for developing the creativity of the company's employees is proven, which is based on the principle of phasing, when the next stage is logically connected to the previous one and is aimed at consolidating what has been achieved and its further development at the next stage.
Keywords: creative thinking; competition; methods of creative thinking